An Enhanced Machine Learning Model for Predicting Stability in Decentralized Power Grids Integrated with Renewable Energy Resource - Urvashi Tembhurnikar; Prof. Ashish Murchikar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The increasing integration of renewable energy resources into decentralized power grids presents significant challenges to maintaining grid stability due to their intermittent and unpredictable nature. Accurately predicting grid stability is crucial to ensuring reliable power delivery and preventing blackouts. This paper proposes an enhanced machine learning model designed to predict stability in decentralized power grids with high penetration of RERs. The model leverages [add a sentence about what data the model leverages, for example: historical grid data, weather forecasts, and real-time sensor measurements]. By incorporating [mention any unique features or techniques of your model, for example: advanced feature engineering techniques, ensemble learning methods, or a novel deep learning architecture], the proposed model aims to achieve higher prediction accuracy compared to existing methods. The performance of the model is evaluated using [mention your evaluation datasets and metrics, for example: real-world grid data from [location] and metrics such as accuracy, precision, and recall]. The results demonstrate the effectiveness of the enhanced model in accurately predicting grid stability, providing valuable insights for grid operators to proactively manage and mitigate potential stability issues in decentralized power grids with high RER integration. To further enhance your abstract, consider adding a sentence about the specific types of renewable energy resources you are focusing on (e.g., solar, wind) and the potential benefits of your model for grid operators.